2023
DOI: 10.3390/ijms241814390
|View full text |Cite
|
Sign up to set email alerts
|

A Route for Investigating Psoriasis: From the Perspective of the Pathological Mechanisms and Therapeutic Strategies of Cancer

Xingkang Wu,
Yushuang Ma,
Lu Wang
et al.

Abstract: Psoriasis is an incurable skin disease that develops in about two-thirds of patients before the age of 40 and requires lifelong treatment; its pathological mechanisms have not been fully elucidated. The core pathological process of psoriasis is epidermal thickening caused by the excessive proliferation of epidermal keratinocytes, which is similar to the key feature of cancer; the malignant proliferation of cancer cells causes tumor enlargement, suggesting that there is a certain degree of commonality between p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 129 publications
0
4
0
Order By: Relevance
“…This mechanism is particularly significant in autoimmune arthritic conditions, including rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis [ 21 ]. Targeting MAPK pathways has been explored as a therapeutic strategy for psoriasis [ 20 , 22 ]. Inhibitors of MAPK pathways, such as JNK inhibitors, ERK inhibitors, and p38 MAPK inhibitors, are being investigated for their potential to control the inflammatory and proliferative processes associated with psoriasis [ 23–26 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism is particularly significant in autoimmune arthritic conditions, including rheumatoid arthritis, ankylosing spondylitis, and psoriatic arthritis [ 21 ]. Targeting MAPK pathways has been explored as a therapeutic strategy for psoriasis [ 20 , 22 ]. Inhibitors of MAPK pathways, such as JNK inhibitors, ERK inhibitors, and p38 MAPK inhibitors, are being investigated for their potential to control the inflammatory and proliferative processes associated with psoriasis [ 23–26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Further research has suggested that increased susceptibility to cancer in psoriasis patients is considered to be affected by factors, such as impaired immune surveillance, immunomodulatory therapy, chronic inflammation, obesity, and other commonly shared risk factors [ 3 , 5 ]. Abnormal immunoinflammatory microenvironment and cell proliferation form a vicious cycle that plays a role in psoriasis and cancer, promoting keratinocyte proliferation in psoriasis and tumor cell proliferation in cancer [ 6 8 ]. In the past decades, studies on the mechanism of the two diseases have mainly focused on immune and inflammatory abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…It is linked to various comorbidities, including a higher risk of early atherosclerosis in patients, the buildup of plaque in arteries leading to cardiovascular diseases. Additionally, psoriasis has been associated with other inflammatory conditions, such as inflammatory bowel disease, which indicates that it may have a broader impact on the body beyond just the skin and joints [4].…”
Section: Introductionmentioning
confidence: 99%
“…This suggests 1 that some common factors may be shared between psoriasis and cancer, such as dysregulated cell signaling pathways and immune dysfunction. Further research is needed to fully understand the complex interplay between these factors and their contribution to the development and progression of psoriasis [4].…”
Section: Introductionmentioning
confidence: 99%